EVALUASI KUALITAS PELAYANAN RUMAH SAKIT PKU MUHAMMADIYAH SURAKARTA DALAM MENINGKATKAN KEPUASAN PASIEN - Marfungatun, Nia; Sukirman, Sukirman; Ngadiman, Ngadiman (MIIPS, 2008)
The purpose of this research is to know: (1) The hospital service standard of PKU Muhammadiyah Surakarta, (2) The patientâs perception to the service quality given by the hospital of PKU Muhammadiyah Surakarta, (3) The harmonistic between the hospital service standard of PKU Muhammadiyah Surakarta with the service quality that has been given to the patient, (4) The obstacles faced by the hospital of PKU Muhammadiyah Surakarta in evaluating the service quality, (5) The solutions for the obstacles in evaluating the service quality. According to the objectives of this study, this research applies qualitative descriptive method. This research uses purposive sampling technique, where the samples taken are not decided by the number of the samples but it is emphasized on the samples understanding quality to the case observed. The samples of the research are the number that represents the information in taking the conclusion. The technique used in collecting data is interview, observation and documentation. The technique of data validity used is source triangulation and method triangulation. Technique of analyzing data used is the interactive data analysis technique. Derived from the analysis, it can conclude that, (1) The hospital service standard of PKU Muhammadiyah Surakarta refers to the accreditation of five service, (2) The patientâs perception to the service quality, (3) The harmonistic between the hospital service standard of PKU Muhammadiyah Surakarta refers to five accreditations of hospital services of PKU Muhammadiyah Surakarta and the service quality dimension. (4) Obstacles faced by the hospital. (5) The solutions for the obstacles.